Processing of Lanting Production Waste as Economic Strengthening for IKM Lanting, Kuwarasan District, Kebumen: Pengolahan Limbah Produksi Lanting sebagai Penguatan Ekonomi IKM Lanting Kecamatan Kuwarasan, Kebumen - Fitri Damayanti; Mashudi Alamsyah; Tulus Widjajanto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities with partner of lanting SMEs in Kuwarasan District, Kebumen Regency, Central Java. Partner problems were dealing with lanting production waste, namely cassava peel, cassava juice liquid waste, and used cooking oil. Generally, these wastes were thrown away so that was causing environmental problems. Therefore, it was necessary to make efforts to treat waste into a product that has economic value. In this activity, science and technology transfer was carried out to process waste into products of economic value, including: liquid organic fertilizer, chips and beef jerky, and solid soap. This activity was expecting to help lanting SMEs survive and rise during the Covid-19 pandemic. In addition, partners were able to reduce the problem of waste pollution from lanting production, increase the economic value of waste, and create new side entrepreneurs besides lanting as an effort to increase economic strengthening and community empowerment.